Regeneración clonal de alcornoques selectos mediante embriogénesis somática (V Congreso Forestal Español, 2009)
Para implementar la silvicultura multivarietal se precisa disponer de una metodología de propagación vegetativa eficiente y económicamente viable. La embriogénesis somática se está asentando como la vía de clonación más adecuada para las especies forestales consideradas recalcitrantes. En el IMIDRA hemos logrado poner a punto un protocolo de inducción de embriogénesis somática en hojas de alcornoques adultos, aplicable a cualquier genotipo, que permite clonar árboles selectos. En el marco del proyecto SEFEAL-2, liderado por TRAGSA, se está aplicando este protocolo con el objetivo de clonar 70 árboles seleccionados por su calidad y productividad en procedencias extremeñas, a fin de establecer los oportunos ensayos clonales que permitan evaluar dicho material para su inclusión en el Catálogo Nacional de Materiales de Base, en la categoría controlado. Hasta el momento se ha trabajado con 59 genotipos, en 51 de ellos se han obtenido brotes epicórmicos y por tanto hojas para inducir embriogénesis, lográndose líneas embriogénicas en 44 de estos últimos. Por tanto, al primer intento se ha logrado la inducción en un 86% de los genotipos ensayados. Se indujo embriogénesis en un 17 % de las hojas introducidas en cultivo, variando la frecuencia con el genotipo entre 0 y 56%. Las líneas se amplificaron por embriogénesis recurrente y los embriones, tanto madurados espontáneamente como sometidos a un tratamiento de maduración, fueron estratificados y dispuestos a germinar. Los porcentajes de conversión a plántula oscilaron en función del genotipo entre el 37 y el 75% para los embriones sometidos a un tratamiento de maduración, y entre el 9 y el 87% para los madurados espontáneamente. La supervivencia media de las vitroplantas regeneradas de embriones que maduraron espontáneamente fue del 17%, variando en función del genotipo entre 0 y 33%, mientras que las que procedieron de embriones somáticos sometidos a tratamiento de maduración fue del 26%, oscilando entre el 12 y el 52% según genotipos. Palabras

First data from a field trial of Quercus suber plants regenerated from mature selected trees and from their half-sib progenies by somatic embryogenesis (Proceedings of the Second International Symposium on Acclimatization and Establishment of Micropropagated Plants, 2007)
Somatic embryogenesis is considered as the most suitable current regeneration technique for the conservation and genetic improvement of tree species. The ability to induce somatic embryogenesis in leaves from mature trees gives the possibility to compare the performance of the parent trees and their progenies at the same age and place of test. Somatic seedlings were regenerated from five selected cork oak trees and from young plants of their half-sib progenies. They were planted in the field conjointly with zygotic seedlings of these families, to test the comparisons somatic vs. zygotic origin and somatic from mature trees vs. somatic from juvenile seedlings. The effect of genotype and kind of progeny will be studied in a complete factorial design; therefore the field trial comprised 15 treatments arranged in five completely randomised blocks. Each experimental unit included three plants that were distributed following a row and column pattern. Fist survival and height data after six and twelve months of establishment are provided. All plants from seeds survived while almost the half of somatic seedlings died after the winter and they were replaced. Almost 70% of these plants survived after the following summer. There were no differences between somatic seedlings of mature or juvenile origin. Zygotic seedlings doubled the height of the somatic ones after one year in the field, and within these plants those of mature origin grew slightly more than those of juvenile source. Differences due to genotype and family effects were noticeable. No apparent morphological alterations were detected among the three kinds of tested progenies.

Vegetative propagation of Quercus suber L. by somatic embryogenesis. II. Plant regeneration from selected cork oak trees. (Plant cell reports, 2003)
The regeneration of somatic seedlings from selected 100-year-old cork oak trees is reported. The induction of somatic embryogenesis from leaves of epicormic shoots was significantly affected by genotype, harvesting time and their interaction. Leaves from all five selected trees produced somatic embryos when the segments of branches used as sources of epicormic shoots were collected in May. Genotype, but not the level of photosynthetically active radiation, affected the proliferation of the embryogenic lines and the number of detachable embryos that could be obtained from them. Genotype also affected several steps leading to conversion of somatic embryos, from germination to complete acclimatisation of somatic seedlings. Almost 40% of the somatic embryos from all lines germinated, showing coordinated root and shoot growth. Although the mean percentage of recovery for the whole process was low, plants could be regenerated from four of the five trees tested.